PERBANKAN SYARIAH DAN PERTUMBUHAN EKONOMI INDONESIA - Ali Rama (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
The paper empirically examines the dynamic interaction between Islamic banking development, capital market, trade activities, inflation and economic growth in Indonesia using battery of time series techniques. The study documents a long-run equilibrium between Islamic banking, capital market, trade activities, inflation and economic growth. Granger causality test reveals that there is a bidirectional causality between Islamic banking-growth in Indonesia, the finding accords with “the feedback hypothesis” or bidirectional causality view”. Based on the VDCs, the study discovers that the variations in the economic growth rely very much on its own innovation. The finding also shows that Islamic banking financing innovation significantly explains the variation in economic growth. To further promote contributions of Islamic banking to economic growth, the authority should provide friendly policies to accelerate its development in the countryDOI: 10.15408/sjie.v2i1.2372